Laws and Acts of Her Majesties Colony of Rhode Island, and Providence-Plantations Made from the First Settlement in 1636 to 1705, at 23 (1896) - (:unkn) unknown (My University, 1673)
Established a militia in 1673, consisting of persons from 16 to 60 years old Each militiaman was required to "at all times hereafter have on[e] good gun or muskitt Fitt for Service one pound of good powder & thirty bullits at Least." If a son or servant had no valuable estate of his own, his parents or master would be liable for any fines imposed upon him.
Keywords: MILITIAS